"Do not quench the Spirit!" The discourse of the Holy Spirit in earliest Christianity - Peerbolte, Bert Jan Lietaert (HTS teologiese studies, 2015)
The Trinitarian discourse of the 4th and 5th centuries grew out of earlier developments, whilst at the same time reflecting a renewal over against the language of the earliest Christian sources. This article reflects on the way in which early Christianity thought about the Holy Spirit and developed a new discourse on the basis of earlier, Jewish traditions. It situates the development of the idea of the Holy Spirit as God’s presence in past and present within the social history of the developing Christian movement, and shows how this idea was connected to the concept of apostolic succession. Thus, emerging Christianity legitimised itself and its social structures by the theology of the Holy Spirit. Its message was presented as old instead of new, as the Holy Spirit had foretold the Christ event. Its organisation was seen as divinely inspired, because its leaders were thought to be endowed with the Spirit. In this development, the narrative of Luke-Acts has thoroughly influenced the way in which Christianity developed a new discourse to present itself as old.